You are on page 1of 3

Powered by www.myengg.

com

HYPERBOLIC FUNCTIONS
PREVIOUS EAMCET BITS
−1 −1
1. sinh 2 + sinh 3 = x ⇒ cosh x = [EAMCET 2009]

1)
1
2
(
3 5 + 2 10 2)
1
2
3 5 − 2 10 ) ( ) 3)
1
2
(12 + 2 50 ) 4)
1
2
(
12 − 2 50 )
Ans: 3
Sol. cosh x = cosh ( sinh −1 2 + sinh −1 3)

=
1
2
(
12 + 2 50 )
1 + tanh ( x / 2 )
2. [EAMCET 2008]
1 − tanh ( x / 2 )
1) e − x 2) e x 3) 2e x / 2 4) 2e − x / 2
Ans: 2
2
⎛x⎞ ⎛x⎞ ⎛x⎞ ⎡ ⎛x⎞ ⎛ x ⎞⎤
1 + tanh ⎜ ⎟ cosh ⎜ ⎟ + sinh ⎜ ⎟ ⎢cosh ⎜ ⎟ + sinh ⎜ ⎟ ⎥
⎝2⎠ = ⎝2⎠ ⎝2⎠ = ⎣ ⎝2⎠ ⎝ 2 ⎠⎦
Sol.
⎛x⎞ ⎛x⎞ ⎛x⎞ ⎛x⎞ ⎛x⎞
1 − tanh ⎜ ⎟ cosh ⎜ ⎟ − sinh ⎜ ⎟ cosh 2 ⎜ ⎟ − sinh 2 ⎜ ⎟
⎝2⎠ ⎝2⎠ ⎝2⎠ ⎝2⎠ ⎝2⎠
⎛x⎞ ⎛x⎞ ⎛x⎞ ⎛x⎞
= cosh 2 ⎜ ⎟ + sinh 2 ⎜ ⎟ + 2 cosh ⎜ ⎟ sinh ⎜ ⎟ = cosh x + sinh x = e x
⎝2⎠ ⎝2⎠ ⎝2⎠ ⎝2⎠
3. sec h ( sin θ ) =
−1
[EAMCET 2007]
θ θ θ θ
1) log tan 2) log sin 3) log cos 4) log cot
2 2 2 2
Ans: 4
⎛ 1 + 1 − sin 2 θ ⎞
Sol. sec h −1 ( sin θ ) = log ⎜ ⎟
⎜ sin θ ⎟
⎝ ⎠
⎛ 1 + cos θ ⎞
= log ⎜ ⎟ = log ( cot θ / 2 )
⎝ sin θ ⎠
(
log cosh −1 2 )
4. e = [EAMCET 2006]
1) log 2 − 3 ( ) 2) log ( 3−2 ) (
3) log 2 + 3 ) 4) log ( 2 + 5 )
Ans: 3
Sol. e e ( ) = f ( x )
log f x

cosh −1( 2 )
elog e = cosh −1 ( 2 )

{
= log 2 + 22 − 1 }
= log 2 + 3 ( )
1

Powered by www.myengg.com
Powered by www.myengg.com

Hyperbolic Functions
1
5. 2 tanh −1 = [EAMCET 2005]
2
1) 0 2) log 2 3) log 3 4) log 4
Ans: 3
1 1+ x
Sol. tanh −1 x = log
2 1− x
1
1+
∴ 2 tanh −1 x = log 2 = log 3
1
1−
2
⎡ ⎛π ⎞⎤
6. x = log ⎢cot ⎜ + θ ⎟ ⎥ ⇒ sinh x = [EAMCET 2004]
⎣ ⎝4 ⎠⎦
1) tan2θ 2) – tan2θ 3) cot 2θ 4) –cot2θ
Ans: 2
⎛π ⎞ ⎛π ⎞
cot ⎜ + θ ⎟ − tan ⎜ + θ ⎟
Sol. sinh x = ⎝ 4 ⎠ ⎝ 4 ⎠ = − tan 2θ
2
7. sinh −1 ( 23/ 2 ) = …… [EAMCET 2003]

(
1) log 2 + 18 ) (
2) log 3 + 8 ) (
3) log 3 − 8 ) 4) log ( 8 + 27 )
Ans: 2

Sol. sinh −1 ( 23/ 2 ) = log ( )
8 + 1 + 8 = log 3 + 8 ( )
8. sin h ix = [EAMCET 2002]
1) i sinx 2) sin (ix) 3) – sinx 4) i sin(ix)
Ans: 1
eix − e− ix ( cos x + i sin x ) − ( cos x − i sin x )
Sol. sinh ( ix ) = = = i sin x
2 2
9. sec 2 ( tan −1 2 ) + cos ec 2 ( cot −1 3) = [EAMCET 2001]
1) 5 2) 10 3) 15 4) 20
Ans: 3
Sol. Let tan −1 ( 2 ) = α and cot −1 ( 3) = β
tan α = 2; cot β = 3
⇒ sec α = 5;cos ecβ = 10
∴ sec 2 α + cos ec 2β = 5 + 10 = 15
10. cosh 2 + sinh 2 = [EAMCET 2000]
2 2
1) 1/e 2) e 3) 1/e 4) e
Ans: 4
e 2 + e −2 e 2 − e −2
Sol. cosh 2 + sinh 2 = + = e2
2 2
(
11. If cosh −1 x = log e 2 + 3 ,then x = ) [EAMCET 2000]
1) 2 2) 1 3) 3 4) 5

2

Powered by www.myengg.com
Powered by www.myengg.com

Hyperbolic Functions
Ans: 1
(
Sol. log ⎡ x + x 2 − 1 ⎤ = log 2 + 3
⎣ ⎦ )
log ⎡ x + x 2 − 1 ⎤ = log ⎡ 2 + ( 2) − 1⎤
2

⎣ ⎦ ⎢⎣ ⎥⎦
∴x=2

””””

3

Powered by www.myengg.com